MODEL QUANTUM WRITING BERBASIS KECERDASAN INTERPERSONAL DALAM PEMBELAJARAN MENULIS ARTIKEL (EKSPERIMEN KUASI PADA SISWA SMA TALENTA BANDUNG) - Triandy, Rendy; Setia Nugraha, Aries; Rustandi, Adi (STKIP Subang, 2021)
The aim of this research was to determine the profile of learning, the learning process and the effectiveness of the application of quantum writing model based of interpersonal intelligence in teaching high school students write articles on subjects Talenta Bandung High School. The reseach design used is Nonequivalen (pretest-posttest) Control Group Design, which is a quasi-experimental research using all subjects in the study group (intac group) for treatment, instead of using subjects drawn randomly. Data collection instruments used were a matter of a test to measure the ability to write articles and guides observation and interviews. Analysis data technique used was Statistic Descrivtif, t test (paired-sample t-test) and independent sample t-test using SPSS version 22. The results showed that the learning profile is still using the curriculum KTSP, while directing students to the learning process easier to develop ideas into writing through the application of quantum writing model based of interpersonal intelligence. Hypothesis test results mean gain score on the test t-table is 0, 001 is smaller than the real level of testing (Î±) of 0.05, which means that Ho refused and Ha is received, there is a significant difference between the results of the experimental class learning with learning outcomes in control class. This shows that the quantum writing model of based interpersonal intelligence can improve students' ability to write articles in Indonesian subjects in Talenta Bandung high school.